2022
DOI: 10.1039/d1cp05388d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the cooperative effect of solvent: a case study

Abstract: The effect of solvent was investigated at the DFT level, M06-2X/6-31++G(d,p), for the implicit, namely the universal solvent model based on solute electron density (SMD), and hybrid solvation models, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Such hybrid explicit/continuum solvation models are often used in the cases where first solvation shell is considered. [32][33][34] Different from the proposed organic-water clusters involving three H2O molecules, the structural configurations for DFT-D3 computing bond relaxation upon the THF and DMSO being hydrated by 2H2O molecules adapt to the Polarizable Continuum model. They were fully optimized associated with frequency calculations to ensure they are minimum on the potential surface.…”
Section: Dft Quantification Of the Bond Length Variations Upon Hydrationmentioning
confidence: 99%
“…Such hybrid explicit/continuum solvation models are often used in the cases where first solvation shell is considered. [32][33][34] Different from the proposed organic-water clusters involving three H2O molecules, the structural configurations for DFT-D3 computing bond relaxation upon the THF and DMSO being hydrated by 2H2O molecules adapt to the Polarizable Continuum model. They were fully optimized associated with frequency calculations to ensure they are minimum on the potential surface.…”
Section: Dft Quantification Of the Bond Length Variations Upon Hydrationmentioning
confidence: 99%
“…The absence of explicit solvent molecules can lead to less stabilized reaction complexes, thus creating an error by fictitiously reducing reaction barriers. 32,33 On the other hand, the implicit solvent methods are frequently used for the determination of ΔG sol due to their computational cost and adequate definition for the solvent effect depending on the size of the system. 34 In this study, the mechanism proposed by Srivastava et al was investigated using implicit solvent methods and it was shown that it can compete with the mechanism proposed by Lambert et al particularly at elevated temperatures.…”
Section: Papermentioning
confidence: 99%
“…The cooperative effect of DMSO and K 3 PO 4 to promote the etherification at ambient temperature with phenols was further explored by the employment of a wide variety of chloroheteroarenes as well as phenols [11] . Electron‐deficient heteroaryl chlorides such as 2‐chloroquinoxaline, 2‐chlorobenzothiazole, 2‐chloropyrazine and 2‐chlorobenzoxazole reacted efficiently with electron‐rich phenols to provide the coupled products in good to excellent yields ( 3 a – g , Scheme 1, Part A).…”
Section: Introductionmentioning
confidence: 99%